2015
DOI: 10.1002/adfm.201503453
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Targeted Multimodal Optical Imaging with Versatile Cadmium‐Free Quantum Dots

Abstract: The rapid development of fluorescence imaging technologies requires concurrent improvements in the performance of fluorescent probes. Quantum dots have been extensively used as an imaging probe in various research areas because of their inherent advantages based on unique optical and electronic properties. However, their clinical translation has been limited by the potential toxicity especially from cadmium. Here, a versatile bioimaging probe is developed by using highly luminescent cadmium-free CuInSe2/ZnS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…However, low pH can cause the dissociation or oxidation of monodentate thiols . To avoid this dissociation issue, ligands containing a hydrophobic spacer between the thiol and the hydrophilic group have been utilized to create QD dispersions that are stable for over a month . Another strategy to generate homogeneous dispersions under aqueous conditions after organic phase synthesis is to encapsulate the QDs in an amphiphilic polymer.…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, low pH can cause the dissociation or oxidation of monodentate thiols . To avoid this dissociation issue, ligands containing a hydrophobic spacer between the thiol and the hydrophilic group have been utilized to create QD dispersions that are stable for over a month . Another strategy to generate homogeneous dispersions under aqueous conditions after organic phase synthesis is to encapsulate the QDs in an amphiphilic polymer.…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%
“…QD targeting based on the overexpression of cell surface proteins has been reported for breast and pancreatic cancer. Liu et al published a CuInSe 2 /ZnS based core–shell system surface conjugated with Cys–Gly–Lys–Arg–Lys (CGKRK), a peptide that binds to a tumor cell membrane biomarker . They used this system to target mice bearing an orthotopic MCF10CA1a breast cancer xenograft.…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…QDs light emission is a useful property for a lot of medical labeling, imaging or sensing applications such as to distinguish between normal and tumor cells [21] gene therapy studies [22], proteomics [23], etc. From the perspective of virology, QDs are useful tools for providing rapid and sensitive virus detection to facilitate early treatment and monitoring of viral disease.…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%
“…Homing peptides have been considered as the most promising targeting agents for human tumors owing to their several merits, including their relatively small molecular weights, ease of synthesis, low immunogenicity, good biocompatibility, and biodegradable characteristics in vivo. 29 It has been reported that A54 peptide (sequence AGKGTPSLETTP) is the most specific and effective targeting agent to the BEL-7402 human hepatoma carcinoma cell line via cell surface markermediated endocytosis. 30 In this work, we developed a novel tumor cell-specific targeted AuNCs-based drug delivery system (doxorubicin [DOX]-loaded, HA-grafted, and A54 peptide-targeted PEGylated AuNCs, abbreviated as DHTPAuNCs) and then investigated their therapeutic effects for the first time (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%